The Lexical Domains of Ugliness and Aesthetic Horror in the Old English Formulaic Style - Minaya Gómez, Francisco Javier (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2023)
Even though as of late there has been a renewed interest in the aesthetic ideals in early Medieval England, the conceptualisation and experience of ugliness in Old English sources has been largely neglected. Drawing on the recent research carried out on aesthetic emotions and folk aesthetics, and despite the lack of academic materials on artistic and literary canons of ugliness, the purpose of this paper is to look into the terms that rendered the experience of ugliness and its closest emotional response, aesthetic horror, in order to examine how these are employed in poetic texts. The findings from this study evidence a lack of use of terms for negative aesthetic experience in Old English poetry that suggests that the lexical domain of ugliness and related emotional responses were not fundamental constituents of the Old English formulaic style, while the lexical domain of beauty and its responses were. Additionally, this study highlights the fundamentally moral character of the idea of ugliness.